Herpes Zoster and Recurrent Herpes Zoster. (28th January 2017) - Shiraki, Kimiyasu; Toyama, Nozomu; Daikoku, Tohru; Yajima, Misako; ,
Abstract: Background: The incidence of recurrent herpes zoster (HZ) and the relationship between initial and recurrent HZ are not clear. Methods: The Miyazaki Dermatologist Society has surveyed ~5000 patients with HZ annually since 1997. A questionnaire regarding HZ and its recurrence was completed by the dermatologists. Results: A total of 34 877 patients with HZ were registered at 43 clinics between June 2009 and November 2015. Among 16 784 patients seen at 10 of the 43 clinics, 1076 patients (6.41%) experienced recurrence. Herpes zoster was more frequent in female than in male patients (5.27 vs 4.25 in 1000 person-years, P < .001), as was HZ recurrence (7.63% vs 4.73%, P < .001). Two and three recurrences were observed in 49 and 3 patients, respectively. Recurrence in the same dermatome was observed in 16.3% of patients, and more frequently this occurred in the left side ( P = .027). The number of HZ-experienced persons increased with age, and one third of the population had experienced HZ by the age of 80. Conclusions: Recurrent HZ was observed in 6.41% of patients, with a higher incidence in women. Moreover, HZ experience reduced the HZ incidence to 31.7% of the incidence in the HZ-naive population.